The Relationship of Parenting Patterns to the Level of Personal Hygiene Independence Children Aged 4-6 Years in Pandemic - Rachman, Yufa Yustika; Rahmadani, Ni Kadek Aris (BELIA: Early Childhood Education Papers, 2023)
One of the things that has an impact on kids' independence is parenting. Future child development, particularly in terms of personal cleanliness, will greatly benefit from this freedom. Personal hygiene independence should be instilled in children from a young age since it will improve the next generation's quality of life and shield them from various illnesses, particularly in light of the current epidemic. Children's immune systems are still developing, making them more susceptible to a wide range of infections. Skin disorders, viral infections, gastrointestinal disorders, and even diseases that render some body parts inoperable are among the illnesses connected to children's personal hygiene (Amanatillah, 2019). Therefore, parents need to be educated to focus more on their kids' personal cleanliness. This study was conducted at Al Khoiriyah Kindergarten Klareyan during a pandemic to examine the association between parenting styles and the degree of personal hygiene independence of children aged 4-6 years. The method employed in this study is a cross sectional method, which uses data from research variables gathered at a certain point in time. 30 respondents who were selected using the total sampling method made up the sample for this investigation. The result of this study a significant positive and unidirectional relationship between parenting styles and children's level of independence in personal hygiene during a pandemic at Al Khoiriyah Kindergarten in Klareyan, with a significance value of 0.009 0.05 and a Pearson correlation value of 0.470, indicating a moderate degree of relationship between the two variables. The findings of the correlation coefficient test show that parenting generally has a very excellent category of 77%, with the most authoritarian parenting style having a moderately authoritarian category of 80% and the least authoritarian parenting style having a moderate category of 63%. The average category for the child's independence in maintaining personal hygiene throughout the pandemic was 67%. Additionally, the indicators of toilet training, skin and hair cleanliness, dental and oral hygiene, and the use of appropriate health protocols fall under the extremely high category of indicators of children's independence in terms of personal hygiene during the pandemic.